A Comparison of Ordered and Unordered Response Models for Analyzing Road Traffic Injury Severities in the North-Eastern Turkey - Çelik, Ali Kemal; Oktay, Erkan (Periodica Polytechnica Transportation Engineering, 2017)
Road traffic injuries are estimated to be one of the major causes of death worldwide and a majority of them occur in low- and middle income countries. In that respect, further studies that address to determine risk factors that may influence road traffic injury severities in the corresponding countries may contribute the existing road safety literature. This paper determines possible risk factors influencing road traffic injury severity in north-eastern Turkey. For this purpose, a retrospective cross-sectional study is conducted analysing 11,771 traffic accidents reported by the police during the sample period of 2008-2013. As the accident severity is inherently ordered, the data are analysed using both ordered and unordered response models. The estimation results reveal that several driver (age and education level), accident (speeding violation, avoiding manoeuvre and right-of-way rule), vehicle (bus/minivan, single-unit truck/heavy truck, private and single vehicles), temporal (time of day, morning peak, evening peak), environmental (summer and cloudy or rainy weather), geometry (asphalt road and road class type), and control characteristics (presence of crosswalk and traffic lights) were found to have an impact on injury severity. This paper is most probably the first attempt to analyse possible risk factors of road traffic injury severities in Turkey using both ordered and unordered response models. The evidence of this study may be valuable for future road safety policies in emerging countries.